2020
DOI: 10.1016/j.ajog.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality among women with coronavirus disease 2019 admitted to the intensive care unit

Abstract: Maternal mortality among women with coronavirus disease 2019 admitted to the intensive care unit OBJECTIVE:Limited data are available on critically ill pregnant women hospitalized with coronavirus disease 2019 (COVID-19). Although maternal mortality has been reported, 1e3 the frequency with which this devastating outcome occurs is unknown. The objective of this study was to determine the rate of maternal death among pregnant and postpartum women with COVID-19 admitted to the intensive care units (ICUs) in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 9 publications
3
80
1
6
Order By: Relevance
“…While COVID-19 is less often severe in children and pregnant women [13,14], these groups would bear a disproportionate burden of excess malaria mortality arising from COVID-19-related disruption of health systems and malaria control programmes, particularly in sub-Saharan Africa. Recently, the Malaria Atlas Project modelled these potential impacts in Africa for the World Health Organization's (WHO) Global Malaria Program [15].…”
Section: Anticipated Impacts Of Covid-19 On Malaria Control and Burdenmentioning
confidence: 99%
“…While COVID-19 is less often severe in children and pregnant women [13,14], these groups would bear a disproportionate burden of excess malaria mortality arising from COVID-19-related disruption of health systems and malaria control programmes, particularly in sub-Saharan Africa. Recently, the Malaria Atlas Project modelled these potential impacts in Africa for the World Health Organization's (WHO) Global Malaria Program [15].…”
Section: Anticipated Impacts Of Covid-19 On Malaria Control and Burdenmentioning
confidence: 99%
“…Subsequent data emerging from Europe and North America also concluded that pregnant women were at no increased risk of severe COVID‐19 or death 3,7,8 . More recently, further studies reported higher risk of ICU admission and mechanical ventilation during pregnancy, 9,10 and the first cases of near miss and maternal deaths have emerged from Iran, US, UK, France, Mexico and Spain 7–9,11–16 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Laboratory ndings consistently included lymphopenia, leukopenia, thrombocytopenia, and elevated levels of C-reactive protein and transaminases. 2,[7][8][9] Others reported an increased D-dimer level and neutrophil/lymphocyte ratio and a decreased white blood cell count. 3,4 Chest CT scans revealed abnormal imaging features, namely ground-glass opacities, in the lungs of pregnant individuals with COVID-19, 2,5,10 but the clinical signi cance of these imaging ndings and the laboratory parameters is not clear.…”
Section: Main Text Direct Effects On Pregnancymentioning
confidence: 99%
“…Most cases of COVID-19 among pregnant individuals did not progress to severe disease, and ICU admission involving mechanical ventilation was seldom required. 1,2,11 The most commonly reported adverse outcome was preterm delivery; [6][7][8]12 and increased prevalence of low birthweight and Cesarean-section (C-section) delivery were also observed, 5,13 although these were not studies representative for well-de ned study bases. Other obstetric complications and outcomes including maternal death, stillbirth, miscarriage, preeclampsia, fetal growth restriction, coagulopathy, and premature rupture of membranes were rare, but apparent.…”
Section: Main Text Direct Effects On Pregnancymentioning
confidence: 99%